The phenotype of alveolar macrophages and its correlation with immune cells in bronchoalveolar lavage - Stríz, I; Wang, Y M; Svarcová, I; Trnka, L; Sorg, C; Costabel, U (The European respiratory journal, 1993)
The phenotype of alveolar macrophages (AMs) is known to be modulated during pathological immune reactions in the lung. In this study, we wanted to determine the relationship between the AM phenotype and changes in the proportions of the various immune cells in bronchoalveolar lavage (BAL). BAL was performed in 76 consecutive patients, including 32 with sarcoidosis, 8 with idiopathic pulmonary fibrosis, 9 with pneumoconiosis, 13 with other respiratory disorders, and 14 controls without evidence of interstitial lung disease. The phenotype of AMs was studied by a panel of 15 monoclonal antibodies against various myeloid antigens, and was correlated with the proportions of cells obtained by BAL. The percentage of BAL lymphocytes showed a relationship with the expression of macrophage antigens in 11 out of 15 antigens studied (all except adhesive molecules CD11a, CD11c, CD18 and the antigen 25F9 present on mature macrophages). Furthermore, the CD4/CD8 ratio of BAL T-lymphocytes correlated with the AM expression of CD54 (intercellular adhesion molecule-1 (ICAM-1)), RFD1 (marker of dendritic cells), and CD71 (transferrin receptor). In samples with an increased number of bronchoalveolar neutrophils, the subpopulation of 27E10 positive AMs (inflammatory acute phase macrophages) was increased. Eosinophils in BAL were not associated with a significant increase in AM membrane antigen expression. Prominent changes of the AM phenotype were found in active sarcoidosis showing lymphocytic alveolitis, with more frequent expression of CD54, KiM2, CD71, CD11b and RFD9. In conclusion, this study shows that the phenotype of AMs is related to the type and intensity of the immunopathological reaction in the lung, and correlates with the proportions of bronchoalveolar cells.
Keywords: Antigens, CD; prezentace antigenu; CD antigeny; Humans; počet leukocytů; Sarcoidosis, Pulmonary; podskupiny lymfocytů; imunofenotypizace; intersticiální plicní nemoci; Bronchoalveolar Lavage Fluid; lidé; plicní nemoci; Leukocyte Count; Cell Adhesion Molecules; Antigen Presentation; Immunophenotyping; Lymphocyte Subsets; mezibuněčná adhezivní molekula-1; Lung Diseases; molekuly buněčné adheze; bronchoalveolární lavážní tekutina; Macrophages, Alveolar; plicní sarkoidóza; Lung Diseases, Interstitial; Intercellular Adhesion Molecule-1; Smoking; kouření; alveolární makrofágy